Penyempurnaan Desain dan Pembuatan Shock Breaker Belakang Tipe Pegas Sepeda Listrik - Alhafi Faidh Alisfahani; Syamsul Hadi; Dimas Adam Wijaya; Aura Krisna Jati; Fengky Adie Perdana; Pipit Wahyu Nugroho; Talifatim Machfuroh (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The problem lies in the load lock from the wheel arm, the BLDC motor whose distance cannot be adjusted, and the flywheel whose movement is less smooth than the original design. The purpose of refining the design is to obtain smooth movement and the position of the load lock from the wheel arm, the BLDC motor that can be adjusted to be ergonomic and optimal. The method of refining the design and manufacture of the rear shock breaker spring type electric bicycle through the stages of working load analysis, the need for the distance of the load setting position and the BLDC motor, calculating the construction strength, manufacturing components, assembling components, and evaluating the results of the shock breaker manufacture. The results of refining the design and manufacture of the rear shock breaker spring type electric bicycle show that the movement of the load lock position from the wheel arm and the BLDC motor is smooth, the flywheel must be balanced, the dimensions of the shock breaker device are 120 cm long, 49.5 cm wide, 155 cm high, 120 rpm rotation speed, 2 cm shock breaker movement distance, and 1.5 cm sideways movement deviation which implies being able to provide adequate damping for electric bicycle riders well.